2013
DOI: 10.1074/jbc.m112.427245
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis by N-Acetyl-d-glucosaminylphosphatidylinositol De-N-acetylase (PIG-L) from Entamoeba histolytica

Abstract: Background: E. histolytica PIG-L is active even in absence of metal, unlike other homologs. Metal stimulation of activity alters V max , not K m . Metal does not alter optimum pH of catalysis. What explains these differences? Results: Conserved Asp-46 and His-140 participate in a general acid-base pair mechanism, unusual for de-N-acetylases. Conclusion: PIG-L of amoeba is significantly different from mammalian PIG-L. Significance: We have identified a probable drug target for selective delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 14 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…Activity is expressed as a percentage relative to the purified OsGLYI-8 without any exogenous addition of metal ions (taken as 100%). requirement for metal ions for catalysis (Ashraf et al, 2013). A possible explanation for this came through mutagenesis studies, which suggested that in the absence of metal ions (primarily Mg 2+ and Mn 2+ ), the active site residues, His and Asp, can participate as a general acid-base pair, therefore effectively abolishing the strict requirement for the metal ion, which can, however, stimulate the activity of PIG-L over the metal-depleted form (Ashraf et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Activity is expressed as a percentage relative to the purified OsGLYI-8 without any exogenous addition of metal ions (taken as 100%). requirement for metal ions for catalysis (Ashraf et al, 2013). A possible explanation for this came through mutagenesis studies, which suggested that in the absence of metal ions (primarily Mg 2+ and Mn 2+ ), the active site residues, His and Asp, can participate as a general acid-base pair, therefore effectively abolishing the strict requirement for the metal ion, which can, however, stimulate the activity of PIG-L over the metal-depleted form (Ashraf et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…requirement for metal ions for catalysis (Ashraf et al, 2013). A possible explanation for this came through mutagenesis studies, which suggested that in the absence of metal ions (primarily Mg 2+ and Mn 2+ ), the active site residues, His and Asp, can participate as a general acid-base pair, therefore effectively abolishing the strict requirement for the metal ion, which can, however, stimulate the activity of PIG-L over the metal-depleted form (Ashraf et al, 2013). In the case of OsGLYI-8 too, highly similar results were found wherein the enzyme was active in the near absence of metal ions while the activity was stimulated upon exogenous addition of divalent cations post-EDTA treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Upon substrate binding, one water molecule is displaced. However, it has been reported that mutation of this general catalytic base does not change the enzymatic activity of the Entamoeba histolytica PIG-L protein in vitro (Ashraf et al, 2013). 4), and a nucleophilic attack takes place after which a tetrahydral oxyanion intermediate is formed.…”
Section: Discussionmentioning
confidence: 99%
“…DnpA is a putative de-N-acetylase Ashraf et al, 2013). The proteins typically display low overall sequence identity (~25%) but share a catalytic site containing a number of conserved residues that are essential for enzymatic activity.…”
Section: Dnpa Does Not Cause Major Lps Modificationsmentioning
confidence: 99%
See 1 more Smart Citation